High durability and low toxicity antimicrobial coatings fabricated by quaternary ammonium silane copolymers. (4th November 2015) - Li, Hairui; Bao, Hongqian; Bok, Ke Xin; Lee, Chi-Ying; Li, Bo; Zin, Melvin T.; Kang, Lifeng
Abstract : Novel quaternary ammonium silane (QAS) antimicrobial copolymers with improved biocompatibility can form transparent and durable coatings via a thermal-curing process. Abstract : Adhesion and subsequent growth of microorganisms on material surfaces are a major concern in many biomedical applications. Currently, various polymers are immobilized on material surfaces to prevent microbial colonization. However, there are several challenges with regard to the coating materials, including their inability to kill microorganisms, complexity of surface grafting, limited durability and toxicity towards humans. To address these challenges, we synthesize a novel quaternary ammonium silane (QAS) antimicrobial copolymer to confer the antimicrobial effect via a simple thermal-curing coating process. The QAS copolymers were less toxic to 3 human cell lines than a commercial antimicrobial QAS monomeric agent, namely, dimethyloctadecyl[3-(trimethoxysilyl) propyl]ammonium chloride (DTPAC). Moreover, the QAS coatings demonstrated superior antimicrobial efficacy and durability than those of the DTPAC coatings. In conclusion, the novel QAS copolymers are useful to prevent substrates from microbial infections, yet with low toxicity to humans and long durability. In addition, the synthetic process is potentially scalable for industrial applications.